Phase II Randomized Trial of Transoral Surgery and Low-Dose Intensity Modulated Radiation Therapy in Resectable p16+ Locally Advanced Oropharynx Cancer: An ECOG-ACRIN Cancer Research Group Trial (E3311). Issue 2 (10th January 2022) - Ferris, Robert L.; Flamand, Yael; Weinstein, Gregory S.; Li, Shuli; Quon, Harry; Mehra, Ranee; Garcia, Joaquin J.; Chung, Christine H.; Gillison, Maura L.; Duvvuri, Umamaheswar; O'Malley, Bert W.; Ozer, Enver; et al.
Abstract : PURPOSE: Definitive or postoperative chemoradiation (CRT) is curative for human papillomavirus–associated (HPV+) oropharynx cancer (OPC) but induces significant toxicity. As a deintensification strategy, we studied primary transoral surgery (TOS) and reduced postoperative radiation therapy (RT) in intermediate-risk HPV+ OPC. METHODS: E3311 is a phase II randomized trial of reduced- or standard-dose postoperative RT for resected stage III-IVa (American Joint Committee on Cancer-seventh edition) HPV+ OPC, determined by pathologic parameters. Primary goals were feasibility of prospective multi-institutional study of TOS for HPV+ OPC, and oncologic efficacy (2-year progression-free survival) of TOS and adjuvant therapy in intermediate-risk patients after resection. TOS plus 50 Gy was considered promising if the lower limit of the exact 90% binomial confidence intervals exceeded 85%. Quality of life and swallowing were measured by functional assessment of cancer therapy-head and neck and MD Anderson Dysphagia Index. RESULTS: Credentialed surgeons performed TOS for 495 patients. Eligible and treated patients were assigned as follows: arm A (low risk, n = 38) enrolled 11%, intermediate risk arms B (50 Gy, n = 100) or C (60 Gy, n = 108) randomly allocated 58%, and arm D (high risk, n = 113) enrolled 31%. With a median 35.2-month follow-up for 359 evaluable (eligible and treated) patients, 2-year progression-free survival Kaplan-Meier estimate is 96.9% (90% CI, 91.9 to 100) for arm A (observation), 94.9% (90% CI, 91.3 to 98.6]) for arm B (50 Gy), 96.0% (90% CI, 92.8 to 99.3) for arm C (60 Gy), and 90.7% (90% CI, 86.2 to 95.4) for arm D (66 Gy plus weekly cisplatin). Treatment arm distribution and oncologic outcome for ineligible or step 2 untreated patients (n = 136) mirrored the 359 evaluable patients. Exploratory comparison of functional assessment of cancer therapy-head and neck total scores between arms B and C is presented. CONCLUSION: Primary TOS and reduced postoperative RT result in outstanding oncologic outcome and favorable functional outcomes in intermediate-risk HPV+ OPC.